The Role of Influencer Gratification in Driving Customer Value Co-Creation: A Study of The Beauty Industry on Social Media - Mutiara Kamilatu Naimah; I Komang Bayu Arta Jaya (proceedings.icesy, 2026)
This study examines the influence of consumer gratifications on brand image with value co-creation as a mediating variable, using the Uses and Gratifications Theory (UGT). In Indonesia’s growing digital marketplace, social media platforms such as Instagram, YouTube, and TikTok have become key channels for consumers to seek information, entertainment, social interaction, and self-expression. A quantitative method was applied by distributing online questionnaires to young digital users, generating 328 valid responses. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results show that all gratification dimensions significantly affect value co-creation, with information gratification having the strongest impact. Value co-creation also significantly influences brand image and mediates the relationship between consumer gratifications and brand image. These findings highlight the importance of encouraging active consumer participation in value co-creation to strengthen brand perceptions in Indonesia’s competitive digital environment.